2022
DOI: 10.11604/pamj.2022.41.3.32403
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of diarrheal diseases in Sierra Leone, 2019: a cross-sectional study

Abstract: Introduction: many studies have shown that unimproved water sources, inadequate sanitation facilities and poor hygiene are the main causes of diarrheal diseases, especially in developing countries. The aim of this study was to determine the prevalence and risk factors associated with diarrheal diseases in Sierra Leone. Methods: a cross-sectional study was conducted in March 2019. We used a questionnaire to collect data from study participants. Descriptive statistical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…This study also examined risk perceptions and WASH-related practices including diarrheal disease risk factors such as demographic, water, sanitation, hygiene, knowledge, and practices. Various studies have revealed that water, sanitation, demographic, and behavioural factors significantly predict diarrheal disease occurrence (14,25,26). Nearly all of the study subjects emphasized the importance of hand washing, suggesting that the MOHS's WASH-related intervention was effective.…”
Section: Discussionmentioning
confidence: 94%
“…This study also examined risk perceptions and WASH-related practices including diarrheal disease risk factors such as demographic, water, sanitation, hygiene, knowledge, and practices. Various studies have revealed that water, sanitation, demographic, and behavioural factors significantly predict diarrheal disease occurrence (14,25,26). Nearly all of the study subjects emphasized the importance of hand washing, suggesting that the MOHS's WASH-related intervention was effective.…”
Section: Discussionmentioning
confidence: 94%
“…The high frequency of use of these facilities is likely to encourage the contamination of adult users with infectious agents and, thus, the transmission of pathogenic agents from adult users to children. 53 This provides evidence in favour of increasing household access to basic sanitation services to combat diarrhoea in children under 5 years. Furthermore, as in the present study, we have not come across any studies that have observed an association between the level of access to sanitation and ARI in children under 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…As for limited sanitation services, although they are based on improved technologies, they have the disadvantage of being shared with other households. The high frequency of use of these facilities is likely to encourage the contamination of adult users with infectious agents and, thus, the transmission of pathogenic agents from adult users to children 53. This provides evidence in favour of increasing household access to basic sanitation services to combat diarrhoea in children under 5 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diarrheal illness is a serious health problematic international [1]. It is perhaps one of the most important reasons of sickness and death amongst infants and broods in developing countries [2]. Recent worldwide estimations suggest that diarrhea kills around 3.2 million under five children each year with a per child average of 3-4 acute chapters per year.…”
Section: Introductionmentioning
confidence: 99%